Development of a Local Culture-Based Creative Thinking Instrument in Science Education using the Rasch Model - Dini Indriyani; Rizki Nor Amelia (SEARCH: Science Education Research Journal, 2026)
Creative thinking skills are important in 21st-century science education, but the availability of contextual and empirically tested assessment instruments is still limited, especially for material on substances and their changes. This study aims to develop an instrument for creative thinking skills in the form of essay questions integrated with local culture in Semarang. The instrument was developed based on four indicators of creative thinking, namely fluency, flexibility, originality, and elaboration, and consisted of seven contextual questions. Content validity was assessed by five experts using Aiken's V index, which produced an average Aiken’s V value of .92, indicating a very high level of item suitability. The instrument was then tested on 175 junior high school students and analyzed using the Rasch Model. The analysis results showed item reliability of .98, indicating extreme stability in the items' difficulty hierarchy. All items were declared fit for the model with outfit and infit mean square values within the accepted criteria range. The response category structure analysis showed a monotonically increasing observed average pattern and sequentially ordered category thresholds, although some threshold differences were outside the ideal range. Overall, the developed instrument has good measurement quality and is suitable for assessing creative thinking skills in science within the local culture.